Analisis Keterampilan Mengajar Variasi Pada Mahasiswa Semester 6 PGSD Universitas Muhammadiayah Purworejo - Eva Lasfiani (Jurnal Dharma PGSD, 2021)
This study aims to determine the ability of basic teaching skills, especially the skills of conducting variations in 6th semester students of PGSD Muhammadiyah University Purworejo in the 2020/2021 Academic Year. This type of research is descriptive research with a quantitative approach. The subjects of this study were 13 6th semester students of PGSD Muhammadiyah University Purworejo. The research instrument is in the form of a questionnaire filled out by the observer. The results of this study that overall get an average score of 60.2 and enter the sufficient category. There are two students who are in the sufficient category and there are 11 students who are in the good category. The highest score was achieved by Candra with a score of 74 and was in the good category. The lowest score was achieved by Nimas with a score of 48 which was included in the sufficient category.